Wittgenstein and surprise in mathematics - Simons, Peter (2015)
One of the psychologically strongest motivations for mathematical platonism is the existence of surprises in mathematics. Time and again results have turned up which went contrary to the expectations of even the best qualified. Wittgenstein was always an anti-platonist, so for him there could be no surprising discoveries about mathematical objects as there can be about animals in the Amazon basin or chemicals on Titan. Given the later Wittgenstein’s algorithmic conception of mathematics, it might appear that for him the only legitimate notion of surprise in mathematics must be merely psychological. In this paper I examine whether a less subjective conception is compatible with his position in the philosophy of mathematics.